Daily Intake and Serum Levels of Copper, Selenium and Zinc According to Glucose Metabolism: Cross-Sectional and Comparative Study - Vishwanath Pattan (MDPI AG, 2021)
Trace elements play an important role in metabolism. We compared the daily intake and serum concentrations of copper (Cu), selenium (Se), and zinc (Zn) across a spectrum of glucose tolerance status in a representative U.S. population. Daily intake and serum concentrations of Cu, Zn and Se in 5087 adults from the 2011–2016 National Health and Nutrition Examination Survey (NHANES) were examined and compared to normal (NGT) and abnormal (AGT) glucose tolerance and the presence of diabetes mellitus (DM). Other than Zn deficiency (21.15%), the prevalence of Zn, Se, and Cu excess and Se and Cu deficiency were low (<4.00%). As compared to the NGT group, Cu and Se supplementation was higher in the AGT and DM groups (p < 0.0001 for all). Serum Se and Zn, but not Cu, concentrations were highly correlated with daily intake (p < 0.0001 for both). As compared to the NGT group, serum Cu concentration was highest in the AGT group (p = 0.03), serum Se concentration was highest in the DM group (p < 0.0001), and serum Zn concentration was highest in the AGT group (p < 0.0001). Serum Se and Zn concentration was correlated with daily Se and Zn intake. Even within the reference range for serum Cu, Se, and Zn concentrations, a higher serum concentration of Cu, Se, and Zn was associated with abnormal glucose metabolism. Although the casual relationship remains to be elucidated, these data suggest caution in Cu, Se and Zn supplementation in non-deficient individuals.